2007
DOI: 10.1021/jp066450g
|View full text |Cite
|
Sign up to set email alerts
|

Donor−Acceptor Distance-Dependence of Photoinduced Electron-Transfer Rate in Flavoproteins

Abstract: Ultrafast fluorescence quenching of flavin in flavodoxin from Megasphaera elsdenii was investigated by means of a fluorescence up-conversion method. Fluorescence lifetimes of flavodoxin from M. elsdenii were estimated to be tau(1) approximately 165 fs (0.97%) and tau(2) approximately 10 ps (0.03%). Correlation of photoinduced electron-transfer rates (k(ET)) with averaged distances (D(av)) between isoalloxazine and nearby tryptophan or tyrosine was examined and obtained an empirical equation of ln k(ET) vs D(av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(73 citation statements)
references
References 41 publications
3
69
1
Order By: Relevance
“…Based on the similar architecture of the chicken RfBP and the dodecin binding pockets, we suggest also that in the dodecins HsDod A and HhDod B the indole moieties of the adjacent tryptophans transfer the electron for RF quenching. Considering the tryptophan-isoalloxazine distances of 3.3 Å in the HsDod A and the HhDod B binding pockets, which are shorter than the respective distances of tryptophan (Trp 156 )-isoalloxazine (3.7 Å) and tyrosine (Tyr 75 )-isoalloxazine (3.7 Å) in the chicken RfBP, electron transfer can be estimated to take place within the sub-picosecond time scale (26,27).…”
Section: Time-resolved Spectroscopy Performed On the Dodecins Rf/hsdodmentioning
confidence: 99%
“…Based on the similar architecture of the chicken RfBP and the dodecin binding pockets, we suggest also that in the dodecins HsDod A and HhDod B the indole moieties of the adjacent tryptophans transfer the electron for RF quenching. Considering the tryptophan-isoalloxazine distances of 3.3 Å in the HsDod A and the HhDod B binding pockets, which are shorter than the respective distances of tryptophan (Trp 156 )-isoalloxazine (3.7 Å) and tyrosine (Tyr 75 )-isoalloxazine (3.7 Å) in the chicken RfBP, electron transfer can be estimated to take place within the sub-picosecond time scale (26,27).…”
Section: Time-resolved Spectroscopy Performed On the Dodecins Rf/hsdodmentioning
confidence: 99%
“…It was found by means of picosecond [19,20] and femtosecond-resolved [21] transient absorption spectroscopy that ET processes from Trp or Tyr to the excited Iso in flavoproteins were responsible for the quenching. Fluorescence decays of several flavoproteins, which were believed to be non-fluorescent, were observed in the time domain of femtoseconds/picoseconds by a fluorescence up-conversion technique [22][23][24][25][26][27]. An empirical equation for ET rate was derived as a function of average distance, R, rather than edge to edge distance, between Iso and nearby Trp or Tyr in flavoproteins [25].…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the donor-acceptor interaction is very strong in CT state, and then the ion pair cannot form. The ''bell shape" of ET rate in the R-representation was also suggested in the flavoprotein systems [14].…”
Section: Discussionmentioning
confidence: 76%
“…In the previous work [13,14] we found that the average distance between both chromophores, rather than edge-to-edge distance, plays an important role for ET.…”
Section: Discussionmentioning
confidence: 82%